Pomegranate Peel Extract Sensitizes Hepatocellular Carcinoma Cells to Ionizing Radiation, Induces Apoptosis and Inhibits MAPK, JAK/STAT3, β-Catenin/NOTCH, and SOCS3 Signaling - Mustafa M. M. Elbakry PhD; Nermeen M. ElBakary PhD; Sanaa A. Hagag PhD; Eman H. A. Hemida PhD (Integrative Cancer Therapies, 2023)
Tumor resistance is typically blamed for the failure of radiotherapy and chemotherapy to treat cancer in clinic patients. To improve the cytotoxicity of tumor cells using radiation in conjunction with specific tumor-selective cytotoxic drugs is crucial. Pomegranate has received overwhelmingly positive feedback as a highly nutritious food for enhancing health and treating a variety of ailments. In the present study, we aimed to examine the effects as well as mechanism of action of pomegranate peel extract (PPE) and/or γ-radiation (6-Gy) on hepatocellular carcinoma (HCC) cell lines HepG2. The findings of this study showed that PPE treatment of HepG2 cells considerably slowed the proliferation of cancer cells, and its combination with γ-irradiation potentiated this action. As a key player in tumor proliferation, and inflammatory cascade induction, the down-regulation of STAT3 following treatment of irradiated and non-irradiated HepG2 cells with PPE as recorded in the present work resulted in reduction of tumor growth, via modulating inflammatory response manifested by (down-regulation of TLR4 expression and NFKB level), suppressing survival markers expressed by reduction of JAK, NOTCH1, β-catenin, SOCS3, and enhancing apoptosis (induction of tumor PPAR-γ and caspase-3) followed by changes in redox tone (expressed by increase in Nrf-2, SOD and catalase activities, and decrease in MDA concentration). In conclusion, PPE might possess a considerable therapeutic potential against HCC in addition to its capability to enhance response of HepG2 cells to gamma radiation,